The rise of the western Armenian diaspora in the early modern Ottoman Empire - Shapiro, Henry R. (Edinburg)
xii, 324 sayfa
Keywords: “The Rise of the Western Armenian Diaspora in the Early Modern Ottoman Empire traces how Armenian migrants changed the demographic and cultural landscape of Istanbul and Western Anatolia in the course of the 17th century. During the centuries that followed, Ottoman Armenian merchants, financiers (sarraf), authors, musicians, translators, printers and bureaucrats would play key roles in Ottoman trade, art and even governance – that is, in most spheres of the empire's economic and cultural life. This book shows how that cosmopolitan world came into being“ --